Nano-microporous composite aerogel material and preparation process thereof

By introducing modified PTFE dispersion, SiO2 sol, magnetic hydrophobic modifier, self-healing microcapsules and reinforcement fibers into SiO2 aerogel materials, and using specific processes to form nano-porous composite aerogel materials, the shortcomings in mechanical properties and high temperature stability of aerogel materials in the prior art are solved, and the stability and fatigue resistance of the material in the repeated impact environment are improved.

CN120137333AInactive Publication Date: 2025-06-13XINXIANG VOCATIONAL & TECHN COLLEGE

Patent Information

Application Number
CN202510625174.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-15
Publication Date
2025-06-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

There are multiple bottlenecks in existing SiO2 aerogel materials in mechanical properties, high temperature stability and practical applications, especially in the weak bonding force between fiber and aerogel, easy layering under long-term cyclic loads, and performance attenuation caused by microcrack propagation.

Method used

A nano-porous composite aerogel material (PTFE/SiO2) was designed. By adding modified PTFE dispersion, SiO2 sol, magnetic hydrophobic modifier, self-healing microcapsules and reinforcement fibers, and using plasma-induced graft polymerization, magnetic field directional composite, gradient freeze forming and surface modification, materials with excellent mechanical properties and self-healing ability are formed.

Benefits of technology

The interface bonding force between the reinforced fiber and the composite aerogel is significantly improved, the stratification phenomenon is avoided, the stability of the material in a repeated impact environment is enhanced, and the expansion of microcracks is suppressed through self-healing microcapsules, improving the fatigue resistance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a nano-microporous composite aerogel material and a preparation process thereof, and belongs to the technical field of aerogel materials, the composite aerogel material comprises modified PTFE dispersion liquid, SiO2 sol, a magnetic hydrophobic modifier, self-repairing microcapsules, reinforced fibers and a surface modifier. The double-shell structure of the self-repairing microcapsule provides excellent mechanical strength and chemical stability, and the self-repairing microcapsule can crack and release the siloxane prepolymer core material during microcrack propagation. The PTFE dispersion liquid is pretreated through plasma-initiated graft polymerization, so that the interface bonding force between the reinforced fiber and the composite aerogel is remarkably improved. According to the treatment method, a chemical bonding layer is formed on the surface of the fiber, and the mechanical interlocking and chemical bonding force of an interface are enhanced, so that the layering phenomenon is avoided, and the stability of the material in a repeated impact environment is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aerogel materials, and particularly relates to a nano-microporous composite aerogel material and a preparation process thereof. Background Art

[0002] The research and development background of the nano-microporous PTFE / SiO 2 composite aerogel material stems from multiple bottlenecks of traditional SiO 2 aerogel materials in mechanical properties, high-temperature stability and practical applications.

[0003] Although the prior art improves the mechanical properties through fiber or polymer composites, the following problems still exist: Although glass fiber or carbon fiber can improve the compressive strength of the composite aerogel material, the interfacial bonding force between the fiber and the aerogel is weak, and it is easy to delaminate under long-term cyclic loading; in addition, the propagation of microcracks in the aerogel leads to long-term performance attenuation, and the plastic deformation increases after undergoing multiple fatigue tests, further affecting its stability in a repeated impact environment.

[0004] Based on this, the present invention designs a nano-microporous composite aerogel material and a preparation process thereof to solve the above problems. Summary of the Invention

[0005] In view of the above-mentioned drawbacks of the prior art, the present invention provides a nano-microporous composite aerogel material (PTFE / SiO 2 ) and a preparation process thereof.

[0006] To achieve the above object, the present invention is realized through the following technical solutions: A nano-microporous composite aerogel material (PTFE / SiO 2 ), by weight, comprises the following components: 100-110 parts of modified PTFE dispersion; 50-80 parts of SiO 2 sol; 20-28 parts of magnetic hydrophobic modifier, including Fe 3 O 4 nano-particle and silane coupling agent complex; 8-10 parts of self-healing microcapsules, including polyurethane-silica double shell and siloxane prepolymer core material; 10-30 parts of reinforcing fiber, and the reinforcing fiber is cellulose nanofiber with a diameter of 5-20 nm after TEMPO oxidation; 5-7 parts of surface modifier, including 80-90% fluorosilane and 10-20% guar gum.

[0007] A said nano-microporous composite aerogel material (PTFE / SiO2 Preparation process of (), comprising the following steps: S1: Mix a siloxane monomer containing an active group with an epoxy resin prepolymer, add dibutyltin dilaurate as a catalyst, and stir and react under nitrogen protection to form a transparent viscous siloxane prepolymer solution; Dissolve the siloxane prepolymer in dichloromethane, add isophorone diisocyanate and polyethylene glycol as a polyurethane prepolymer, and stir evenly to obtain an oil phase; Dissolve polyvinyl alcohol in deionized water, and add sodium dodecyl sulfate as an emulsifier to obtain an aqueous phase; Dropwise add the oil phase into the aqueous phase, perform ultrasonic emulsification, raise the temperature, add diethylenetriamine as a chain extender, and react to form microcapsules coated with polyurethane; Mix tetraethyl orthosilicate with ethanol, add hydrochloric acid to adjust the pH to 3-4, and hydrolyze to form a SiO 2 precursor sol, disperse the microcapsules coated with polyurethane in the SiO 2 precursor sol, dropwise add ammonia water, stir at room temperature, and make the SiO 2 form a dense shell on the surface of the polyurethane through a condensation reaction; Perform gas-phase treatment on the SiO 2 shell with perfluorooctyltriethoxysilane to obtain self-healing microcapsules; Collect the self-healing microcapsules by centrifugation, and wash them successively with ethanol and deionized water to remove unreacted monomers and surfactants; S2: Pretreat the PTFE matrix; Mix the PTFE dispersion with ammonium perfluorooctanoate, and perform ultrasonic treatment to form a stable micelle structure; Add acrylate monomers, and carry out graft polymerization by plasma initiation to obtain a modified PTFE dispersion; S3: Prepare a magnetic hydrophobic modifier; Mix Fe 3 O 4 nanoparticles with KH560 silane coupling agent in ethanol and react for 2-4 h to obtain a magnetic hydrophobic modifier; Mix the magnetic hydrophobic modifier with SiO 2 sol, and perform gas-phase treatment with fluorosilane; S4: Magnetic field-oriented composite, mix the modified PTFE dispersion, reinforcing fibers and SiO 2 sol, and stir for 20-40 min under an alternating magnetic field; S5: Gradient freeze forming, use an ethanol-tert-butanol mixed solvent to displace the wet gel, cool down in stages and then mix with the self-healing microcapsules; S6: Drying and curing, vacuum drying at -60 to -80 °C for 24 - 48 h, and then stepwise heating and curing under nitrogen protection to obtain the precursor of the nano-porous composite aerogel material (PTFE / SiO 2 ). S7: Surface modification, impregnating with a fluorosilane solution after plasma treatment, and reacting at 60 - 80 °C for 4 - 8 h to obtain the nano-porous composite aerogel material (PTFE / SiO 2 ).

[0008] Furthermore, the fluorosilane is selected from at least one of heptadecafluorodecyltrimethoxysilane, perfluorodecyltriethoxysilane, or tridecafluorooctyltriethoxysilane.

[0009] Furthermore, S1 is specifically as follows: Mix a siloxane monomer containing active groups and an epoxy resin prepolymer in a mass ratio of 1:1.5 - 2, add 0.5% - 1% of dibutyltin dilaurate as a catalyst, and stir and react at 60 - 80 °C for 4 - 6 h under nitrogen protection to form a transparent viscous siloxane prepolymer solution; Dissolve the siloxane prepolymer in dichloromethane (mass ratio 1:5), add isophorone diisocyanate and polyethylene glycol as a polyurethane prepolymer, and the mass ratio of the three is 1:0.8:0.5, and stir evenly to obtain an oil phase; Dissolve polyvinyl alcohol in deionized water (concentration 2% - 5%), and add 0.1% of sodium dodecyl sulfate as an emulsifier to obtain an aqueous phase; Dropwise add the oil phase into the aqueous phase, perform ultrasonic emulsification, heat up to 70 °C, add diethylenetriamine as a chain extender (mass ratio of isophorone diisocyanate:diethylenetriamine = 1:0.3), and react for 3 h to form microcapsules coated with polyurethane; Mix tetraethyl orthosilicate and ethanol in a ratio of 1:4, add 0.1 M hydrochloric acid to adjust the pH to 3 - 4, and hydrolyze for 30 min to form a SiO2 precursor sol. Disperse the microcapsules coated with polyurethane in the SiO 2 precursor sol, dropwise add ammonia water until pH = 9, and stir at room temperature for 12 h to form a dense shell on the surface of the polyurethane through a condensation reaction; 2 Perform gas-phase treatment on the SiO shell with perfluorooctyltriethoxysilane at 100 °C for 2 h to make the contact angle of the shell ≥ 150° to obtain self-healing microcapsules; 2 Collect the self-healing microcapsules by centrifugation (3000 rpm, 10 min), wash them 3 times with ethanol and deionized water in turn to remove unreacted monomers and surfactants; Perform vacuum freeze-drying (-50 °C, 24 h), and sieve (particle size range 20 - 50 μm).

[0010] ​Further, S2 specifically includes: mixing the PTFE dispersion and ammonium perfluorooctanoate in a mass ratio of 1:0.3 - 0.5, and performing ultrasonic treatment at 40 - 60 °C for 30 - 60 min to form a stable micelle structure; Adding acrylate monomers accounting for 10 - 40% of the mass of the PTFE dispersion, and conducting plasma-induced graft polymerization to obtain a modified PTFE dispersion. After the acrylate monomers in the modified PTFE dispersion are grafted through plasma induction, a cross-linked network is formed; Coating the PTFE dispersion on a glass slide or a Teflon substrate to form a uniform thin film (with a thickness of 50 - 100 μm), and pre-drying at 80 °C for 30 min to remove the solvent in the PTFE dispersion; Under an argon flow rate of 20 - 50 sccm, a vacuum degree of ≤50 Pa, and a power of 50 - 100 W, performing plasma treatment for 2 - 5 min. After the plasma treatment ends, introducing acrylate monomer vapor into the vacuum chamber, heating the monomer to 60 - 80 °C, controlling the monomer partial pressure to be 10 - 50 Pa, and infiltrating for 10 - 30 min to enable the monomer to adsorb onto the active surface of the PTFE. Immersing the plasma-treated PTFE film into an acrylate monomer solution (with a concentration of 5 - 20 wt%), and using ultrasonic assistance (40 kHz, 10 min) to promote the diffusion of the monomer to the micropores on the PTFE surface; In an argon atmosphere, activating the combination of the monomer and the free radicals on the PTFE surface. The plasma excites the double bonds in the monomer molecules, initiating a free radical chain reaction, enabling the acrylate to graft onto the PTFE chain and forming a covalent cross-linked network.

[0011] Further, S3 specifically includes: preparing a magnetic hydrophobic modifier; Reacting Fe 3 O 4 nanoparticles and KH560 silane coupling agent in ethanol for 2 - 4 h. The mass ratio of Fe 3 O 4 nanoparticles to ethanol is 1:20 - 25 to obtain a magnetic hydrophobic modifier; Mixing the magnetic hydrophobic modifier with SiO 2 sol, and performing gas-phase treatment with a fluorosilane at 80 - 120 °C for 2 - 3 h, with a contact angle ≥155°.

[0012] Further, S5 specifically includes: using a mixed solvent of modified PTFE dispersion and ethanol - tert-butanol with a volume ratio of 1:1 - 3 to displace the wet gel (immersing the wet gel in the mixed solvent, changing the solvent in 3 times, driving the exchange of water molecules and organic solvents through a concentration gradient. When the gel volume no longer changes significantly and the water content in the solvent is lower than 1%, it is considered that the displacement is completed); performing staged cooling in the following steps: The first stage: Cool down to -20 to 0 °C at a rate of 1 - 5 °C / min. The slow cooling promotes the formation of a macroporous structure. At the same time, the eutectic point of ethanol and tert-butanol is relatively low (about -20 °C), which inhibits the growth of ice crystals. The second stage: Cool down to -80 to -60 °C at a rate of 5 - 10 °C / min. The rapid cooling fixes the microstructure, reduces the extrusion of the pore channels by solvent crystallization, and forms uniform nanoscale pores, and then mixes with self-healing microcapsules.

[0013] Furthermore, S6 is specifically: S7: Surface modification. After plasma treatment (argon atmosphere, 50 - 100 W, 5 - 10 min), immerse it in a fluorosilane solution (concentration 0.1% - 1.5%), and react at 60 - 80 °C for 4 - 8 h to obtain a nano-microporous composite aerogel material (PTFE / SiO 2 ).

[0014] Use a vacuum plasma treatment device, select a radio frequency source with a radio frequency of 13.56 MHz, select argon as the process gas, and control the flow rate at 20 - 50 sccm to ensure that the chamber vacuum degree ≤ 50 Pa; Under the power of 50 - 100 W of the vacuum plasma treatment device, treat for 5 - 10 min, maintain the chamber temperature ≤ 40 °C, and bombard the PTFE surface with argon ions to form a micro-nano rough structure by physical etching; The high-energy particles in the plasma break the C-F bonds of the PTFE molecular chain, generating free radicals and active groups (such as -COOH, -OH), enhancing the surface chemical activity; Dissolve the surface modifier in a 90% ethanol-water mixed solution, with the mass concentration of the surface modifier being 0.1% - 1.5%, and add 0.1% - 0.5% acetic acid to adjust the pH to 4 - 5 to promote the hydrolysis of silane; Immerse the precursor of the nano-microporous composite aerogel material (PTFE / SiO 2 ) in anhydrous ethanol and ultrasonically clean for 5 - 10 min to remove residual pollutants, dry at 70 - 80 °C for standby, and immerse the precursor of the nano-microporous composite aerogel material (PTFE / SiO 2 ) vertically into the fluorosilane solution (avoiding the retention of air bubbles); Keep it in a constant temperature water bath at 60 - 80 °C for 4 - 8 h, drain for 30 min, and rinse twice with ethanol (to remove the unreacted silane physically adsorbed); Under nitrogen protection, cure in an oven at 60 - 80 °C for 2 - 3 h to promote the formation of the Si-O-Si network.

[0015] Compared with the prior art, the beneficial effects of the present invention are: 1. The self-healing microcapsules of the present invention are composed of a polyurethane-silica double-shell structure and a siloxane prepolymer core material. The double-shell structure provides excellent mechanical strength and chemical stability, and can rupture and release the siloxane prepolymer core material when microcracks propagate. This design not only protects the stability of the core material during material preparation and use, but also ensures the timely release of the healing agent when cracks are triggered.

[0016] 2. The present invention pre-treats the PTFE dispersion by plasma-induced graft polymerization, significantly improving the interfacial bonding strength between the reinforcing fibers and the composite aerogel. This treatment method forms a chemical bonding layer on the fiber surface, enhancing the mechanical interlocking and chemical bonding strength at the interface, thus avoiding delamination and further improving the stability of the material in a repeated impact environment.

[0017] 3. The stepwise cooling process of the present invention can optimize the microstructure of the material, making the surface energy distribution more uniform, thereby enhancing the stability of the hydrophilic property. By controlling the cooling rate of the material, the formation and propagation of cracks are reduced, thus improving the fatigue resistance of the material.

[0018] 4. The synergistic effect between the self-healing microcapsules and the pre-treatment step of the PTFE dispersion further improves the comprehensive performance of the composite aerogel. The pre-treatment of the PTFE dispersion enhances the interfacial bonding strength between the reinforcing fibers and the aerogel matrix, avoiding delamination, while the self-healing microcapsules inhibit the propagation of microcracks. This synergistic mechanism enables the composite aerogel to simultaneously possess excellent mechanical properties and hydrophilic properties in a repeated impact environment. Detailed implementation mode

[0019] To make the objectives, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are some, but not all, of the embodiments of the present invention. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.

[0020] Example 1: This example provides a nano-porous composite aerogel material (PTFE / SiO 2 ), by weight, including the following components: 110 parts of modified PTFE dispersion, 80 parts of SiO 2 sol; 28 parts of magnetic hydrophobic modifier, including Fe 3 O 4 nanoparticle and silane coupling agent complex; 10 parts of self-healing microcapsules, including a polyurethane-silica double shell and a siloxane prepolymer core material; 30 parts of reinforcing fibers, and the reinforcing fibers are cellulose nanofibers with a diameter of 20 nm after being oxidized by TEMPO (2,2,6,6-tetramethylpiperidine-N-oxyl radical); 7 parts of surface modifier, including 90% fluorosilane and 10% guar gum.

[0021] The preparation process of the nano-porous composite aerogel material (PTFE / SiO 2 ) includes the following steps: S1: Mix a siloxane monomer with active groups (heptadecafluorodecyltrimethoxysilane) and an epoxy resin prepolymer in a mass ratio of 1:2, add 1% of dibutyltin dilaurate as a catalyst, and under nitrogen protection, stir and react at 80 °C for 6 h to form a transparent viscous siloxane prepolymer solution; Dissolve the siloxane prepolymer in dichloromethane (mass ratio 1:5), add isophorone diisocyanate and polyethylene glycol as polyurethane prepolymers, and the mass ratio of the three is 1:0.8:0.5, and stir evenly to obtain an oil phase; Dissolve polyvinyl alcohol in deionized water (concentration 5%), and add 0.1% of sodium dodecyl sulfate as an emulsifier to obtain an aqueous phase; Dropwise add the oil phase into the aqueous phase, perform ultrasonic emulsification (5000 rpm, 10 min), raise the temperature to 70 °C, add diethylenetriamine as a chain extender (mass ratio of isophorone diisocyanate:diethylenetriamine = 1:0.3), and react for 3 h to form polyurethane-coated microcapsules; Mix tetraethyl orthosilicate (TEOS) and ethanol in a ratio of 1:4, add 0.1 M hydrochloric acid to adjust the pH to 4, and hydrolyze for 30 min to form a SiO 2 precursor sol, disperse the polyurethane-coated microcapsules in the SiO 2 precursor sol, dropwise add ammonia water until pH = 9, stir at room temperature for 12 h, and make SiO 2 form a dense outer shell on the surface of the polyurethane through a condensation reaction; Perform a 2 h gas-phase treatment on the SiO 2 outer shell at 100 °C to make the contact angle of the outer shell ≥ 150°, and obtain self-healing microcapsules; Collect the self-healing microcapsules by centrifugation (3000 rpm, 10 min), and wash them 3 times with ethanol and deionized water in sequence to remove unreacted monomers and surfactants; Vacuum freeze-dry (-50 °C, 24 h), and sieve (particle size range 50 μm); S2: Pretreat the PTFE matrix; Mix a 5% PTFE dispersion and ammonium perfluorooctanoate in a mass ratio of 1:0.5, and perform ultrasonic treatment at 60 °C for 60 min to form a stable micelle structure; Add acrylate monomers accounting for 40% of the mass of the PTFE dispersion liquid, and through plasma-initiated graft polymerization, a modified PTFE dispersion liquid is obtained. After the acrylate monomers in the modified PTFE dispersion liquid are grafted by plasma initiation, a cross-linked network is formed; Coat the PTFE dispersion liquid on a glass slide or a Teflon substrate to form a uniform film (thickness 100 μm), and pre-dry it at 80 °C for 30 min to remove the solvent in the PTFE dispersion liquid; Under an argon flow rate of 50 sccm, a vacuum degree of ≤50 Pa, and a power of 100 W, perform plasma treatment for 5 min. After the plasma treatment is completed, introduce acrylate monomer vapor into the vacuum chamber. By heating the monomer to 80 °C and controlling the monomer partial pressure to be 50 Pa, allow it to penetrate for 30 min to adsorb the monomer onto the active surface of PTFE. Immerse the plasma-treated PTFE film into an acrylate monomer solution (concentration 20 wt%), and use ultrasonic assistance (40 kHz, 10 min) to promote the diffusion of the monomer into the micropores on the PTFE surface; In an argon atmosphere, activate the combination of the monomer and the free radicals on the PTFE surface. The plasma excites the double bond (C=C) in the monomer molecule, initiating a free radical chain reaction, so that the acrylate is grafted onto the PTFE chain to form a covalent cross-linked network.

[0022] S3: Prepare a magnetic hydrophobic modifier; Mix Fe 3 O 4 nanoparticles and KH560 silane coupling agent in ethanol and react for 4 h. The mass ratio of Fe 3 O 4 nanoparticles to ethanol is 1:25 to obtain a magnetic hydrophobic modifier; Mix the magnetic hydrophobic modifier with SiO 2 sol, and perform gas-phase treatment at 120 °C for 3 h with a fluorosilane (such as perfluoroalkylsilane or trimethylchlorosilane), and the contact angle ≥155°; S4: Magnetic field-directed compounding. Mix the modified PTFE dispersion liquid, reinforcing fibers and SiO 2 sol, and stir for 40 min under an alternating magnetic field (0.3 T, frequency 5000 Hz); The preparation method of the reinforcing fibers is as follows: Disperse cellulose nanofibers in 50 times the volume of deionized water, stir for 30 min to form a uniform suspension, successively add TEMPO and NaBr, stir and dissolve them, then slowly dropwise add NaClO solution, monitor the pH change, and control and maintain the pH between 10 - 10.5 by dropwise adding 0.1 M NaOH. When the pH no longer changes, it is the reaction end point. Add 1 / 5 volume of absolute ethanol to terminate the reaction, and stir for 10 min to obtain reinforcing fibers; S5: Gradient freezing forming. Replace the wet gel with a modified PTFE dispersion liquid and an ethanol-tert-butanol mixed solvent with a volume ratio of 1:3 (immerse the wet gel in the mixed solvent, change the solvent 3 times, drive the exchange of water molecules and organic solvents through the concentration gradient. When the gel volume no longer changes significantly and the water content in the solvent is less than 1%, it is considered that the replacement is completed), mix with the self-healing microcapsules after cooling in stages; At 0 °C, the rate is 5 °C / min. Promote the formation of macroporous structures by slow cooling. At the same time, the eutectic point of ethanol and tert-butanol is relatively low (about -20 °C), which inhibits ice crystal growth; At -60 °C, the rate is 10 °C / min. Rapidly cool to fix the microstructure, reduce the extrusion of the pore channels by solvent crystallization, and form uniform nanoscale pores; S6: Drying and curing. Vacuum dry at -60 °C for 48 h, and cure by heating in stages under nitrogen protection (keep at 200 °C for 2 h, keep at 300 °C for 1 h); S7: Surface modification. After plasma treatment (argon atmosphere, 100 W, 10 min), immerse in a fluorosilane solution (concentration 1.5%), react at 80 °C for 8 h to obtain a nano-microporous composite aerogel material (PTFE / SiO 2 ).

[0023] Use a vacuum plasma treatment device, select a radio frequency source with a radio frequency of 13.56 MHz, select argon as the process gas, control the flow rate at 50 sccm, and ensure that the chamber vacuum degree ≤ 50 Pa; Under the power of 100 W of the vacuum plasma treatment device, treat for 10 min, maintain the chamber temperature ≤ 40 °C, and bombard the PTFE surface with argon ions to form a micro-nano rough structure by physical etching; The high-energy particles in the plasma break the C-F bonds of the PTFE molecular chain, generating free radicals and active groups (such as -COOH, -OH), enhancing the surface chemical activity.

[0024] Dissolve the surface modifier in a 90% ethanol-water mixed solution, the mass concentration of the surface modifier is 1.5%, and add 0.5% acetic acid to adjust the pH to 4 to promote silane hydrolysis; Immerse the precursor of the nano-microporous composite aerogel material (PTFE / SiO 2 )) in anhydrous ethanol and ultrasonically clean for 10 min to remove residual pollutants, dry at 80 °C for standby. Immerse the precursor of the nano-microporous composite aerogel material (PTFE / SiO 2 )) vertically into the fluorosilane solution (avoid air bubble residues); Keep in a constant temperature water bath at 80 °C for 8 h, drain for 30 min, and rinse with ethanol 2 times (remove the unreacted silane adsorbed physically); Under nitrogen protection, cure in an oven at 80 °C for 3 h to promote the formation of the Si-O-Si network; The fluorosilane is selected from heptadecafluorodecyltrimethoxysilane.

[0025] Example 2: This example provides a nano-porous composite aerogel material (PTFE / SiO 2 ), by weight, comprising the following components: 100 parts of modified PTFE dispersion; 50 parts of SiO 2 sol; 20 parts of magnetic hydrophobic modifier, including Fe 3 O 4 nanoparticle and silane coupling agent complex; 8 parts of self-healing microcapsules, including polyurethane-silica double shell and siloxane prepolymer core material; 10 parts of reinforcing fibers, and the reinforcing fibers are cellulose nanofibers with a diameter of 5 nm after being oxidized by TEMPO (2,2,6,6-tetramethylpiperidine-N-oxyl radical); 5 parts of surface modifier, including 80% fluorosilane and 20% guar gum.

[0026] The preparation process of the nano-porous composite aerogel material (PTFE / SiO 2 ), comprises the following steps: S1: Mix the siloxane monomer with active groups (heptadecafluorodecyltrimethoxysilane) and the epoxy resin prepolymer in a mass ratio of 1:1.5, add 0.5% dibutyltin dilaurate as a catalyst, and stir and react at 60 °C for 4 h under nitrogen protection to form a transparent viscous siloxane prepolymer solution; Dissolve the siloxane prepolymer in dichloromethane (mass ratio 1:5), add isophorone diisocyanate and polyethylene glycol as polyurethane prepolymers, and the mass ratio of the three is 1:0.8:0.5, and stir evenly to obtain an oil phase; Dissolve polyvinyl alcohol in deionized water (concentration 2%), and add 0.1% sodium dodecyl sulfate as an emulsifier to obtain an aqueous phase; Dropwise add the oil phase into the aqueous phase, perform ultrasonic emulsification (5000 rpm, 10 min), heat up to 70 °C, add diethylenetriamine as a chain extender (mass ratio of isophorone diisocyanate:diethylenetriamine = 1:0.3), and react for 3 h to form polyurethane-coated microcapsules; Mix tetraethyl orthosilicate (TEOS) and ethanol in a ratio of 1:4, add 0.1 M hydrochloric acid to adjust the pH to 3, and hydrolyze for 30 min to form SiO 2 precursor sol, and disperse the polyurethane-coated microcapsules in SiO 2In the precursor sol, ammonia water was added dropwise until pH = 9, and stirred at room temperature for 12 h to form SiO 2 A dense outer shell was formed on the surface of the polyurethane through a condensation reaction; SiO was treated with perfluorooctyltriethoxysilane 2 The outer shell was subjected to a 2-h gas-phase treatment at 100 °C to make the contact angle of the outer shell ≥ 150°, and self-healing microcapsules were obtained; The self-healing microcapsules were collected by centrifugation (3000 rpm, 10 min), washed three times with ethanol and deionized water in turn to remove unreacted monomers and surfactants; Vacuum freeze-drying (-50 °C, 24 h), sieving (particle size range 20 - 50 μm); S2: Pretreat the PTFE matrix; A 5% PTFE dispersion and ammonium perfluorooctanoate were mixed at a mass ratio of 1:0.3 and ultrasonically treated at 40 °C for 30 min to form a stable micelle structure; 10% of acrylate monomer based on the mass of the PTFE dispersion was added, and graft polymerization was initiated by plasma to obtain a modified PTFE dispersion. After the acrylate monomer in the modified PTFE dispersion was grafted by plasma, a crosslinked network was formed; The PTFE dispersion was coated on a glass slide or a Teflon substrate to form a uniform film (thickness 50 μm), and pre-dried at 80 °C for 30 min to remove the solvent in the PTFE dispersion; At an argon flow rate of 20 sccm, a vacuum degree ≤ 50 Pa, and a power of 50 W, plasma treatment was carried out for 2 min. After the plasma treatment was completed, acrylate monomer vapor was introduced into the vacuum chamber. By heating the monomer to 60 °C and controlling the monomer partial pressure to be 10 Pa, permeation was carried out for 10 min to adsorb the monomer to the active surface of the PTFE. The plasma-treated PTFE film was immersed in an acrylate monomer solution (concentration 5 wt%), and ultrasonic assistance (40 kHz, 10 min) was used to promote the diffusion of the monomer to the micropores on the PTFE surface; In an argon atmosphere, the monomer was activated to combine with the free radicals on the PTFE surface. The plasma excited the double bond (C=C) in the monomer molecule, initiating a free radical chain reaction to graft the acrylate onto the PTFE chain and form a covalent crosslinked network.

[0027] S3: Prepare a magnetic hydrophobic modifier; Fe with a mass ratio of 1:0.02 3 O 4 nanoparticles and KH560 silane coupling agent were reacted in ethanol for 2 h. The mass ratio of Fe 3 O 4 nanoparticles to ethanol was 1:20 to obtain a magnetic hydrophobic modifier; Mix the magnetic hydrophobic modifier with SiO 2 sol, and perform gas-phase treatment with a fluorosilane (such as perfluoroalkylsilane or trimethylchlorosilane) at 80 °C for 2 h, with a contact angle ≥ 155°; S4: Magnetic field orientation composite, mix the modified PTFE dispersion, reinforcing fibers with SiO 2 sol, and stir for 20 min under an alternating magnetic field (0.05 T, frequency 500 Hz); S5: Gradient freezing forming, use a mixed solvent of modified PTFE dispersion and ethanol - tert-butanol with a volume ratio of 1:1 to displace the wet gel (immerse the wet gel in the mixed solvent, change the solvent 3 times, drive the exchange of water molecules and organic solvents through the concentration gradient, and consider the displacement completed when the gel volume no longer changes significantly and the water content in the solvent is less than 1%), mix with self-healing microcapsules after staged cooling; At -20 °C at a rate of 1 °C / min, promote the formation of macroporous structures by slow cooling. At the same time, the eutectic point of ethanol and tert-butanol is relatively low (about -20 °C), inhibiting ice crystal growth; At -80 °C at a rate of 5 °C / min, quickly cool to fix the microstructure, reduce the extrusion of the pore channels by solvent crystallization, and form uniform nanoscale pores; S6: Drying and curing, vacuum dry at -60 °C for 24 h, and cure by staged heating under nitrogen protection (keep at 150 °C for 0.5 h, keep at 250 °C for 0.5 h); S7: Surface modification, after plasma treatment (argon atmosphere, 50 W, 5 min), immerse in a fluorosilane solution (concentration 0.1%), and react at 60 °C for 4 h to obtain a nano-porous composite aerogel material (PTFE / SiO 2 ).

[0028] Use a vacuum plasma treatment device, select a radio frequency source with a radio frequency of 13.56 MHz, select argon as the process gas, control the flow rate at 20 sccm, and ensure that the chamber vacuum degree ≤ 50 Pa; Under the power of 50 W of the vacuum plasma treatment device, treat for 5 min, maintain the chamber temperature ≤ 40 °C, bombard the PTFE surface with argon ions, and physically etch to form a micro-nano rough structure; The high-energy particles in the plasma break the C-F bonds of the PTFE molecular chain, generating free radicals and active groups (such as -COOH, -OH), enhancing the surface chemical activity.

[0029] Dissolve the surface modifier in a 90% ethanol - water mixed solution, with the mass concentration of the surface modifier being 0.1%, and add 0.1% acetic acid to adjust the pH to 5 to promote silane hydrolysis; For the nano-porous composite aerogel material (PTFE / SiO 2The precursor is immersed in anhydrous ethanol and ultrasonically cleaned for 5 min to remove residual contaminants, and then dried at 70 °C for standby. The nano-porous composite aerogel material (PTFE / SiO 2 The precursor is vertically immersed in the fluorosilane solution (to avoid air bubble residues); Constant temperature water bath at 60 °C for 4 h, drained for 30 min, and rinsed twice with ethanol (to remove the unreacted silane adsorbed physically); Under nitrogen protection, cured in an oven at 60 °C for 2 h to promote the formation of the Si-O-Si network; The fluorosilane is selected from perfluorodecyltriethoxysilane.

[0030] Example 3: This example provides a nano-porous composite aerogel material (PTFE / SiO 2 ), by weight, including the following components: 104 parts of modified PTFE dispersion, 61 parts of SiO 2 sol; 22 parts of magnetic hydrophobic modifier, including Fe 3 O 4 nano-particle and silane coupling agent complex; 9 parts of self-healing microcapsules, including polyurethane-silica double shells and siloxane prepolymer core material; 15 parts of reinforcing fiber, and the reinforcing fiber is cellulose nanofiber with a diameter of 10 nm after being oxidized by TEMPO (2,2,6,6-tetramethylpiperidine-N-oxyl radical); 6 parts of surface modifier, including 80% fluorosilane and 20% guar gum.

[0031] The preparation process of the nano-porous composite aerogel material (PTFE / SiO 2 ), includes the following steps: S1: Mix the siloxane monomer with active groups (heptadecafluorodecyltrimethoxysilane) and epoxy resin prepolymer in a mass ratio of 1:1.7, add 0.8% of dibutyltin dilaurate as a catalyst, and under nitrogen protection, stir and react at 75 °C for 5 h to form a transparent viscous siloxane prepolymer solution; Dissolve the siloxane prepolymer in dichloromethane (mass ratio 1:5), add isophorone diisocyanate and polyethylene glycol as polyurethane prepolymers, and the mass ratio of the three is 1:0.8:0.5, stir evenly to obtain an oil phase; Dissolve polyvinyl alcohol in deionized water (concentration 3%), add 0.1% of sodium dodecyl sulfate as an emulsifier to obtain an aqueous phase; The oil phase was added dropwise to the water phase, and ultrasonic emulsification was carried out (5000 rpm, 10 min). Then the temperature was raised to 70 °C, and diethylenetriamine was added as a chain extender (mass ratio of isophorone diisocyanate:diethylenetriamine = 1:0.3). The reaction was carried out for 3 h to form microcapsules coated with polyurethane; Tetraethyl orthosilicate (TEOS) and ethanol were mixed at a ratio of 1:4, and 0.1 M hydrochloric acid was added to adjust the pH to 4. Hydrolysis was carried out for 30 min to form a SiO 2 precursor sol. The microcapsules coated with polyurethane were dispersed in the SiO 2 precursor sol, and ammonia water was added dropwise until pH = 9. Stirring was carried out at room temperature for 12 h to form a dense outer shell on the surface of the polyurethane through a condensation reaction; 2 The microcapsules were dispersed in the precursor sol, and ammonia water was added dropwise until pH = 9. Stirring was carried out at room temperature for 12 h to form a dense outer shell on the surface of the polyurethane through a condensation reaction; The SiO 2 outer shell was subjected to a gas-phase treatment at 100 °C for 2 h to make the contact angle of the outer shell ≥150°, and self-healing microcapsules were obtained; The self-healing microcapsules were collected by centrifugation (3000 rpm, 10 min), washed three times with ethanol and deionized water in turn to remove unreacted monomers and surfactants; Vacuum freeze-drying (-50 °C, 24 h), and sieving (particle size range 30 μm); S2: Pretreat the PTFE matrix; A 5% PTFE dispersion and ammonium perfluorooctanoate were mixed at a mass ratio of 1:0.4 and ultrasonically treated at 50 °C for 45 min to form a stable micelle structure; 20% of the acrylate monomer based on the mass of the PTFE dispersion was added, and graft polymerization was initiated by plasma to obtain a modified PTFE dispersion. After the acrylate monomer in the modified PTFE dispersion was grafted by plasma, a crosslinked network was formed; The PTFE dispersion was coated on a glass slide or a Teflon substrate to form a uniform film (thickness 80 μm), and pre-dried at 80 °C for 30 min to remove the solvent in the PTFE dispersion; Under an argon flow rate of 40 sccm, a vacuum degree of ≤50 Pa, and a power of 100 W, plasma treatment was carried out for 5 min. After the plasma treatment was completed, acrylate monomer vapor was introduced into the vacuum chamber. By heating the monomer to 78 °C and controlling the monomer partial pressure to be 30 Pa, penetration was carried out for 25 min to adsorb the monomer to the active surface of the PTFE. The plasma-treated PTFE film was immersed in an acrylate monomer solution (concentration 15 wt%), and ultrasonic assistance (40 kHz, 10 min) was used to promote the diffusion of the monomer to the micropores on the surface of the PTFE; In an argon atmosphere, the activated monomer binds to the free radicals on the PTFE surface. The plasma excites the double bond (C=C) in the monomer molecule, initiating a free radical chain reaction, grafting acrylate onto the PTFE chain, and forming a covalent cross-linked network.

[0032] S3: Prepare a magnetic hydrophobic modifier; React Fe 3 O 4 nanoparticles with KH560 silane coupling agent in ethanol for 2 h. The mass ratio of Fe 3 O 4 nanoparticles to ethanol is 1:23 to obtain a magnetic hydrophobic modifier; Mix the magnetic hydrophobic modifier with SiO 2 sol, and perform gas-phase treatment at 100 °C for 2 h with a fluorosilane (such as perfluoroalkylsilane or trimethylchlorosilane), and the contact angle ≥ 155°; S4: Magnetic field-oriented compounding. Mix the modified PTFE dispersion, reinforcing fiber and SiO 2 sol, and stir for 30 min under an alternating magnetic field (0.2 T, frequency 3000 Hz); S5: Gradient freezing molding. Use a mixed solvent of modified PTFE dispersion and ethanol-tert-butanol with a volume ratio of 1:3 to displace the wet gel (immerse the wet gel in the mixed solvent, change the solvent 3 times, and drive the exchange of water molecules and organic solvents through the concentration gradient. When the gel volume no longer changes significantly and the water content in the solvent is less than 1%, it is considered that the displacement is completed), and mix with self-healing microcapsules after stepwise cooling; At -10 °C with a rate of 2 °C / min, slowly cool down to promote the formation of macroporous structure. At the same time, the eutectic point of ethanol and tert-butanol is relatively low (about -20 °C), which inhibits ice crystal growth; At -70 °C with a rate of 7 °C / min, quickly cool down to fix the microstructure, reduce the extrusion of the pore channels by solvent crystallization, and form uniform nanoscale pores; S6: Drying and curing. Vacuum dry at 72 °C for 24 h, and cure by stepwise heating under nitrogen protection (keep warm at 180 °C for 1 h, keep warm at 260 °C for 1 h); S7: Surface modification. After plasma treatment (argon atmosphere, 100 W, 10 min), impregnate with a fluorosilane solution (concentration 1%), and react at 80 °C for 6 h to obtain a nano-porous composite aerogel material (PTFE / SiO 2 ).

[0033] Use a vacuum plasma treatment equipment, select a radio frequency source with a radio frequency of 13.56 MHz, select argon as the process gas, and control the flow rate at 40 sccm to ensure that the chamber vacuum degree ≤ 50 Pa; Under the condition that the power of the vacuum plasma processing equipment is 90 W, process for 8 min while maintaining the cavity temperature ≤ 40 °C. Bombard the PTFE surface with argon ions to form a micro-nano rough structure through physical etching; High-energy particles in the plasma break the C-F bonds of the PTFE molecular chain to generate free radicals and active groups (such as -COOH, -OH), enhancing the surface chemical activity.

[0034] Dissolve the surface modifier in a 90% ethanol-water mixed solution with a mass concentration of 1% of the surface modifier, and add 0.5% acetic acid to adjust the pH to 4 to promote the hydrolysis of silane; Immerse the precursor of the nano-porous composite aerogel material (PTFE / SiO 2 ) in absolute ethanol and ultrasonically clean for 10 min to remove residual pollutants, then dry at 76 °C for standby. Immerse the precursor of the nano-porous composite aerogel material (PTFE / SiO 2 ) vertically into the fluorosilane solution (avoiding the retention of air bubbles); Keep in a constant temperature water bath at 72 °C for 4 h, drain for 30 min, and rinse twice with ethanol (to remove the unreacted silane adsorbed physically); Under nitrogen protection, cure in an oven at 68 °C for 2 h to promote the formation of the Si-O-Si network; The fluorosilane is selected from tridecafluorooctyltriethoxysilane.

[0035] Comparative Example 1: The difference between this comparative example and Example 3 is that no self-healing microcapsules are added.

[0036] Comparative Example 2: The difference between this comparative example and Example 3 is that the PTFE dispersion is not pretreated.

[0037] Comparative Example 3: The difference between this comparative example and Example 3 is that in S5, instead of cooling down in stages, it is rapidly cooled to -70 °C in one step for molding.

[0038] Comparative Example 4: The difference between this comparative example and Example 3 is that neither self-healing microcapsules are added, nor the PTFE dispersion is pretreated, and in S5, it is not cooled down in stages either, but is rapidly cooled to -70 °C in one step for molding.

[0039] Experimental Example: 1. Density and porosity: Calculate the bulk density of the aerogel by the ratio of the mass and volume of the material, and calculate the skeletal density (g / cm 3 ) and porosity of the aerogel through the formula.

[0040] ρ s =1 / (ω PTFE / ρ PTFE +ω SiO2 / ρ SiO2 ); Porosity = (1 - ρ / ρ s ) × 100%; where ρ is the bulk density of the composite aerogel, and ρ s is the skeletal density of the composite aerogel, with the unit of g / cm 3 ; ρ PTFE is the skeletal density of PTFE, with a value of 2.20 g / cm 3 ; ρ SiO2 is the skeletal density of SiO 2 , with a value of 2.19 g / cm 3 , ω PTFE is the mass ratio of PTFE, and ω SiO2 is the mass ratio of silica sol; 2. Thermal conductivity: The thermal conductivity (W / m·K) of SiO 2 aerogel at room temperature was measured using the transient plane heat source method (TPS2500S, HotDisk, Sweden) to characterize the thermal performance of the material. The smaller the thermal conductivity, the better the heat insulation performance of the material.

[0041] 3. Hydrophobic property: The contact angle (θ 1 ) of the composite aerogel was measured using a fully automatic contact angle measuring instrument (DSA100, Krüss, Germany). After 2000 cycles of bending failure load, the contact angle (θ 2 ) was measured again to judge the hydrophilic and hydrophobic properties of the material based on the size and difference of the two contact angles.

[0042] 4. The pressure P 1 when the deformation rate reaches 10% was detected through the GB / T 34336-2017 index (it should be not less than 200 kPa). After 2000 cycles of bending failure load, the pressure P 2 when the deformation rate reaches 10% was detected again.

[0043]

[0044] As can be seen from the above table, in the present invention, by adding self-healing microcapsules, the propagation of microcracks inside the composite aerogel is inhibited, so that the composite aerogel can maintain a small plastic deformation even after undergoing multiple fatigue tests (the difference between P 1 and P 2 in Comparative Example 1 is greater than that in Examples 1-3); by pretreating the PTFE dispersion through plasma-induced graft polymerization, the interfacial bonding force between the reinforcing fibers and the composite aerogel is improved, thus avoiding delamination of the composite aerogel under long-term cyclic loading, resulting in a reduction in its stability under repeated impact environments (the difference between P 1 and P 2 in Comparative Example 2 is greater than that in Examples 1-3); In addition, the present invention improves the contact angle and the fatigue resistance of the contact angle (the θ of Comparative Example 3 1 is smaller than that of Examples 1-3, and the difference between θ 1 and θ 2 is greater than that of Examples 1-3), that is, the hydrophilic property of the composite aerogel is improved; while the P of Comparative Example 4 1 and P 2 , θ 1 and θ 2 values illustrate that the compounding occurs between the self-healing microcapsules and the pretreatment steps of the PTFE dispersion liquid, which can further improve the stability of the composite aerogel in a repeated impact environment, including the stability of the plastic deformation amount and the contact angle.

[0045] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it; although the present invention has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that: they can still modify the technical solutions recorded in the foregoing embodiments, or perform equivalent replacements on some of the technical features; and these modifications or replacements will not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A nano-microporous composite aerogel material, characterized in that: By weight, it includes the following components: 100-110 parts of modified PTFE dispersion; 50-80 parts of SiO2 sol; 20-28 parts of a magnetic hydrophobic modifier, including a composite of Fe3O4 nanoparticles and a silane coupling agent; 8-10 parts of self-healing microcapsules, including polyurethane-silicon dioxide double shells and siloxane prepolymer core materials; 10-30 parts of reinforcing fibers, wherein the reinforcing fibers are cellulose nanofibers having a diameter of 5-20 nm after TEMPO oxidation; 5-7 parts of surface modifier, including 80-90% fluorosilane and 10-20% guar gum.

2. A process for preparing the nanoporous composite aerogel material according to claim 1, characterized in that: The following steps are involved: S1: Mixing a siloxane monomer containing an active group with an epoxy resin prepolymer, adding dibutyltin dilaurate as a catalyst, stirring and reacting under nitrogen protection to form a transparent and viscous siloxane prepolymer solution; Dissolving a siloxane prepolymer in dichloromethane, adding isophorone diisocyanate and polyethylene glycol as a polyurethane prepolymer, and stirring evenly to obtain an oil phase; Dissolving polyvinyl alcohol in deionized water, adding sodium lauryl sulfate as an emulsifier to obtain an aqueous phase; The oil phase is added dropwise into the water phase, ultrasonically emulsified, heated, and diethylenetriamine is added as a chain extender to react and form polyurethane-coated microcapsules; Mix ethyl orthosilicate with ethanol, add hydrochloric acid to adjust the pH to 3-4, hydrolyze to form SiO2 precursor sol, disperse the polyurethane-coated microcapsules in the SiO2 precursor sol, add ammonia water dropwise, stir at room temperature, and allow SiO2 to form a dense shell on the polyurethane surface through a condensation reaction; The SiO2 shell was treated with perfluorooctyltriethoxysilane in the gas phase to obtain self-healing microcapsules; The self-healing microcapsules were collected by centrifugation and washed with ethanol and deionized water in sequence to remove unreacted monomers and surfactants; S2: pre-treating the PTFE substrate; The PTFE dispersion is mixed with ammonium perfluorooctanoate and subjected to ultrasonic treatment to form a stable micelle structure; Adding acrylate monomers, and initiating graft polymerization by plasma to obtain a modified PTFE dispersion; S3: preparing a magnetic hydrophobic modifier; The Fe3O4 nanoparticles were reacted with a KH560 silane coupling agent in ethanol for 2-4 h to obtain a magnetic hydrophobic modifier; The magnetic hydrophobic modifier is mixed with SiO2 sol and treated with fluorine-containing silane gas phase; S4: Magnetic field oriented compounding, mixing the modified PTFE dispersion, reinforcing fiber and SiO2 sol, and stirring for 20-40 minutes under an alternating magnetic field; S5: Gradient freezing molding, using ethanol-tert-butyl alcohol mixed solvent to replace the wet gel, and mixing it with the self-healing microcapsules after cooling in stages; S6: Drying and curing: vacuum drying at -60 to -80°C for 24-48h, and curing by heating in stages under nitrogen protection to obtain a nano-microporous composite aerogel material precursor; S7: Surface modification: After plasma treatment, immersion in fluorosilane solution and reaction at 60-80°C for 4-8h to obtain nano-microporous composite aerogel material.

3. The preparation process of the nano-microporous composite aerogel material according to claim 2, characterized in that: The fluorosilane is selected from at least one of heptadecafluorodecyltrimethoxysilane, perfluorodecyltriethoxysilane or tridecafluorooctyltriethoxysilane.

4. The preparation process of the nano-microporous composite aerogel material according to claim 2, characterized in that: S1 is specifically as follows: a siloxane monomer containing an active group is mixed with an epoxy resin prepolymer in a mass ratio of 1:1.5-2, 0.5%-1% of dibutyltin dilaurate is added as a catalyst, and the mixture is stirred at 60-80° C. for 4-6 hours under nitrogen protection to form a transparent and viscous siloxane prepolymer solution; Dissolve a siloxane prepolymer in dichloromethane, add isophorone diisocyanate and polyethylene glycol as a polyurethane prepolymer in a mass ratio of 1:0.8:0.5, and stir evenly to obtain an oil phase; Polyvinyl alcohol was dissolved in deionized water, and 0.1% sodium lauryl sulfate was added as an emulsifier to obtain an aqueous phase; The oil phase was added dropwise into the water phase, ultrasonically emulsified, heated to 70°C, and diethylenetriamine was added as a chain extender, and reacted for 3 h to form polyurethane-coated microcapsules; Mix ethyl orthosilicate with ethanol, add hydrochloric acid to adjust the pH to 3-4, hydrolyze to form SiO2 precursor sol, disperse the polyurethane-coated microcapsules in the SiO2 precursor sol, add ammonia water dropwise to adjust the pH, stir at room temperature, and allow SiO2 to form a dense shell on the polyurethane surface; The SiO2 shell was treated with perfluorooctyltriethoxysilane in the gas phase to obtain self-healing microcapsules; The self-repairing microcapsules were collected by centrifugation and washed with ethanol and deionized water in sequence to remove unreacted monomers and surfactants.

5. The preparation process of the nano-microporous composite aerogel material according to claim 2, characterized in that: S2 is specifically as follows: PTFE dispersion and ammonium perfluorooctanoate are mixed in a mass ratio of 1:0.3-0.5, and ultrasonically treated at 40-60°C for 30-60 minutes to form a stable micelle structure; Adding 10-40% of the mass of acrylate monomer to the PTFE dispersion, and performing plasma-induced graft polymerization to obtain a modified PTFE dispersion, wherein the acrylate monomer in the modified PTFE dispersion is grafted by plasma-induced grafting to form a cross-linked network; The PTFE dispersion is coated on a glass slide or a Teflon substrate to form a uniform film, and the solvent in the PTFE dispersion is removed by pre-drying; The plasma treatment is performed for 2-5 minutes at an argon flow rate of 20-50 sccm, a vacuum degree of ≤50 Pa, and a power of 50-100 W. After the plasma treatment, acrylate monomer vapor is introduced into the vacuum chamber, and the monomer is heated to 60-80° C., the monomer partial pressure is controlled to 10-50 Pa, and the permeation is performed for 10-30 minutes to make the monomer adsorb to the active surface of PTFE, and the plasma-treated PTFE film is immersed in the acrylate monomer solution, and ultrasound is used to assist in promoting the diffusion of the monomer to the micropores on the surface of PTFE; In an argon atmosphere, the activated monomer combines with the free radicals on the PTFE surface, and the plasma excites the double bonds in the monomer molecules, triggering a free radical chain reaction, so that the acrylate is grafted onto the PTFE chain to form a covalent cross-linked network.

6. The preparation process of the nano-microporous composite aerogel material according to claim 2, characterized in that: S3 specifically comprises: preparing a magnetic hydrophobic modifier; The Fe3O4 nanoparticles and KH560 silane coupling agent in a mass ratio of 1:0.02-0.05 are reacted in ethanol for 2-4 hours, and the mass ratio of the Fe3O4 nanoparticles to the ethanol is 1:20-25 to obtain a magnetic hydrophobic modifier; The magnetic hydrophobic modifier is mixed with SiO2 sol and treated with fluorine-containing silane vapor at 80-120°C for 2-3h, and the contact angle is ≥155°.

7. The preparation process of the nano-microporous composite aerogel material according to claim 2, characterized in that: S5 specifically comprises: replacing the wet gel with a modified PTFE dispersion and an ethanol-tert-butyl alcohol mixed solvent in a volume ratio of 1:1-3; Perform a phased cooling process with the following steps: The first stage: cooling to -20 to 0°C at a rate of 1-5°C / min, and slowly cooling to promote the formation of macroporous structure; The second stage: cooling to -80 to -60°C at a rate of 5-10°C / min. Rapid cooling fixes the microstructure, reduces the squeezing of the pores by solvent crystallization, forms uniform nanoscale pores, and then mixes with self-healing microcapsules.

8. The process for preparing the nano-microporous composite aerogel material according to claim 2, characterized in that: S7 specifically includes: using vacuum plasma processing equipment, selecting a radio frequency source with a radio frequency of 13.56 MHz, selecting argon as the process gas, controlling the flow rate at 20-50 sccm, and ensuring that the vacuum degree of the chamber is ≤50 Pa; The power of the vacuum plasma treatment equipment is 50-100W, the treatment is carried out for 5-10 minutes, the chamber temperature is maintained at ≤40°C, and the argon ions bombard the PTFE surface to form a micro-nano rough structure by physical etching; The high-energy particles in the plasma break the CF bonds of the PTFE molecular chain, generating free radicals and active groups, which enhance the surface chemical activity; Dissolve the surface modifier in an ethanol-water mixed solution, the mass concentration of the surface modifier is 0.1%-1.5%, add 0.1%-0.5% acetic acid to adjust the pH to 4-5 to promote silane hydrolysis; The nanoporous and microporous composite aerogel material precursor is immersed in anhydrous ethanol for ultrasonic cleaning for 5-10 minutes to remove residual pollutants, and dried at 70-80°C for use, and the nanoporous and microporous PTFE / SiO2 composite aerogel material precursor is vertically immersed in a fluorosilane solution; Place in a 60-80℃ constant temperature water bath for 4-8h, drain for 30min, and rinse twice with ethanol; Under nitrogen protection, cure in an oven at 60-80°C for 2-3 hours to promote the formation of Si-O-Si network.

Citation Information

Patent Citations

  • Ultra-amphiphobic NFC (nano-fibrillated cellulose) aerogel based on directional freezing as well as preparation method and application of NFC aerogel

    CN110183722A

  • Hydrophobic double-shell isocyanate type self-repairing microcapsule as well as preparation method and application thereof

    CN114950293A

Cited By

  • Modified reinforced polytetrafluoroethylene expanded membrane and preparation method thereof

    CN121226800A

  • Insulator steel foot coating layer and preparation process thereof

    CN122158284A

  • Insulator steel foot coating layer and preparation process thereof

    CN122158284B